FRI0545 Treatment with anti IL-1 and Infectious Complications in Paediatric Patients with Systemic Juvenile Idiophatic Arthritis and Autoinflammatoy Diseases. (10th June 2014) - Fernandez-Silveira, L.; Gonzalez, M.; Calvo, I.; Lόpez, B.; Benito, S.
Abstract : Background: Paediatric patients with rheumatic diseases have a higher risk of infections. The treatment with anti-IL 1 drugs (anakinra/canakinumab) can increase the occurrence of infectious diseases Objectives: The aim of this study is to review the infectious complications in children with systemic juvenile idiophatic arthritis (SJIA) or autoinflammatory diseases (AD) while receiving anti-IL1 drugs Methods: The clinical charts of the paediatric patients followed in a Unit of Rheumatic diseases, diagnosed with SJIA or AD from January 2005 to January 2014, in a tertiary hospital in Valencia, Spain, were reviewed Results: Fourty-six patients were identified. Fourty of their clinical charts were available. Their diagnosis were: 30 SJIA, 7 Hiper IgD syndrome (HIDS), 2 tumour necrosis factor receptor-associated periodic fever syndrome (TRAPS), 1 Cryopyrin-Associated Periodic Syndrome (CAPS) and 1 pyogenic arthritis, pyoderma gangrenosum and acne syndrome (PAPA). Thirty six of them had received anakinra and 16 canakinumab. Twenty four had been treated only with anakinra, 4 only with canakinumab and 12 had received both because of initial treatment failure. In the group receiving anakinra 6 major infections (4 pneumonia, 1 VEB infection and 1 sepsis) were recorded and 3 in the canakinumab group (1 pneumonia and 2 soft tissue infections). In the SJIA group 3/30 patients (10%) developed at least one relevant infection: patient 1: 1 major Epstein Bar Virus infection with secondary macrophagic activation syndrome while she was receiving anakinra, patient 2: 3 pneumonia episodes (2 of them with anakinra and 1 with canakinumab) and patient 3: 1 pneumonia episode (treatment with anakinra). AD group: 5/11 (45%) patients developed at least 1 relevant infection: patient 1: pneumonia (treatment with anakinra); patient 2: 1 Herpes Zoster (treatment with canakinumab), patient 3: 4 low UTI (urinary tract infections); patient 4: 2 soft tisues infections while receiving canakinumab, and patient 5: 1 oral candidiasis, sepsis and florid herpetic stomatitis (treatment with canakinumab). Conclusions: Paediatric patients with rheumatic disease being treated with anti IL1 drugs must be carefully followed. They must be advised to search for early medical attention in case they have any symptom of infection. It must be noted that the incidence of infectious diseases is higher in the AD group References: Interleukin-1 receptor antagonist anakinra in patients with systemic-onset juvenile idiopathic arthritis (ANAJIS trial). Quartier P., Allantaz F., Cimaz R., Pascal P., Messiaen C., Bardin Ch., and col. Ann Rheum Dis 2011;70:747–754 Two randomized trials of canakinumab in systemic juvenile idiopathic arthritis. Ruperto N, Brunner HI, Quartier P, Constantin T, Wulffraat N, Horneff G, Brik R, McCann L, Kasapcopur O, Rutkowska-Sak L, Schneider R, Berkun Y, Calvo I, Erguven M, Goffin L, Hofer M, Kallinich T, Oliveira SK, Uziel Y, Viola S, Nistala K, Wouters C, Cimaz R, Ferrandiz MA, Flato B, Gamir ML, Kone-Paut I, Grom A, Magnusson B, Ozen S, Sztajnbok F, Lheritier K, Abrams K, Kim D, Martini A, Lovell DJ; PRINTO; PRCSG.N Engl J Med. 2012 Dec 20;367(25):2396-406. Treating inflammation by blocking interleukin-1 in humans. Dinarello CA1, van der Meer JW. Semin Immunol. 2013 Dec 15;25(6):469-84. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5866